MicroRNA-21 Mediates the Protective Effects of Mesenchymal Stem Cells Derived from iPSCs to Human Bronchial Epithelial Cell Injury Under Hypoxia. Issue 3 (March 2018) - Li, Cheng-Lin; Xu, Zhi-Bin; Fan, Xing-Liang; Chen, He-Xin; Yu, Qiu-Ning; Fang, Shu-Bin; Wang, Shu-Yue; Lin, Yong-Dong; Fu, Qing-Ling
Airway epithelial cell injury is a key triggering event to activate allergic airway inflammation, such as asthma. We previously reported that administration of mesenchymal stem cells (MSCs) significantly alleviated allergic inflammation in a mouse model of asthma, and the mmu-miR-21/ACVR2A axis may be involved. However, whether MSCs protect against bronchial epithelial cell injury induced by hypoxia, and the underlying mechanism, remain unknown. In our study, the human bronchial epithelial cell line BEAS-2B was induced to undergo apoptosis with a hypoxia mimic of cobalt chloride (CoCl2 ) damage. Treatment of MSCs derived from induced pluripotent stem cells (iPSCs) significantly decreased apoptosis of BEAS-2B cells. There was high miR-21 expression in injured BEAS-2B cells after MSC treatment. Transfection of the miR-21 mimic significantly decreased apoptosis of BEAS-2B, and transfection of a miR-21 inhibitor significantly increased apoptosis. More importantly, the protective effects of MSCs on injured BEAS-2B were reversed by transfection of the miR-21 inhibitor. Binding sites of human miR-21 were identified in the 3'UTR of human ACVR2A. We further determined that CoCl2 stimulation increased ACVR2A expression at both the mRNA and protein levels. Moreover, transfection of the miR-21 mimic further up-regulated ACVR2A expression induced by CoCl2, whereas transfection of the miR-21 inhibitor down-regulated ACVR2A expression. In addition, MSCs increased ACVR2A expression in BEAS-2B cells; however, this effect was reversed after transfection of the miR-21 inhibitor. Our data suggested that MSCs protect bronchial epithelial cells from hypoxic injury via miR-21, which may represent an important target. These findings suggest the potentially wide application of MSCs for epithelial cell injury during hypoxia.